Scalable distributed virtual environments using multicast application level - Correia, Ronaldo Celso Messias [UNESP]; Pellegrino, Sergio Roberto M. (Institute of Electrical and Electronics Engineers (IEEE), 2005)
Most of architectures proposed for developing Distributed Virtual Environment (DVE) allow limited number of users. To support the development of applications using the internet infrastructure, with hundred or, perhaps, thousands users logged simultaneously on DVE, several techniques for managing resources, such as bandwidth and capability of processing, must be implemented. The strategy presented in this paper combines methods to attain the scalability required, In special the multicast protocol at application level.
Keywords: DVE; Multicast Application Level; Scalable; Computer software reusability; Internet; Multicasting; User interfaces; Virtual reality; Bandwidth; Computer architecture; Distributed computer systems; Network protocols; Multicast application level; Distributed Virtual Environment (DVE)